PENGARUH KEBIJAKAN SUNSET POLICY DAN TAX AMNESTY TERHADAP EFEKTIVITAS KEMAUAN MEMBAYAR PAJAK (Study Pada KPP PRATAMA DEMAK) - AHMAD NUR SANDI (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
Abstrak This study aims to examine the effect of sunset policy and tax amnesty policy on effectiveness of taxpayer. Independent variables used are sunset policy and tax amnesty and dependent variable effectiveness of taxpayer intention. The purpose of this study is to obtain empirical evidence about the influence of policy variables sunset policy and tax amnesty to the effectiveness of the willingness to pay taxes in KPP Pratama Demak. This research is a quantitative research. The population is all taxpayers in KPP Pratama Demak. The sample of this study amounted to 200 respondents with probability sampling technique with simple random sampling. Simple random sampling. Data collection methods used questionnaires while the analysis technique using regression analysis supported by normality test, multicolonierity and heteroskedasitas test. The result of the research shows that Sunset Policy Policy has a positive effect on the effectiveness of taxpayer willingness. Tax Amnesty has a positive effect on the effectiveness of the willingness to pay taxes. Contribution value of 67.3%. Keywords: Sunset Policy Policy, Tax Amnesty, Tax Payer Effectivenes